Labor skills in the livestock sector of La Pampa: (Licenciatura en Administración de Negocios Agropecuarios) (Semiárida, 2022)
The agricultural sector does not escape the complexity that exists in the search for human resources that occurs throughout the labor market. This complexity motivated us to explore the situation in the livestock sector of La Pampa by testing the instrument designed for this purpose (semi-directed interview, skills cards). To carry out this exploratory analysis, the research has been limited to microregion No. 6 of the province of La Pampa (classification of the Ministry of Territorial Development). As a starting point, a relatively new concept was incorporated into the designed tool: "job competencies" and was reinforced with other important human resources concepts such as compensation and training. A theoretical sample was carried out with a total of 10 interviews that we segmented according to the agrarian social typology of Mercedes De Basco. With this field study, it was possible to know in an exploratory way the work skills demanded by the livestock establishments in the province of La Pampa, as well as to gather the degree of development that the current staff has with respect to them. This methodology allowed the designed instrument to be tested and approved and lay the foundations for subsequent studies.Director: Lasheras, Daniel MarioCo-Director: Rovatti, Guido
Keywords: cattle raising